Diagnosability of the exchanged crossed cube. Issue 2 (3rd April 2018) - Zhou, Dongfang; Fan, Jianxi; Zhou, Jingya; Wang, Yan; Cheng, Baolei
ABSTRACT: The -dimensional exchanged crossed cube combines the strong points of the exchanged hypercube and the crossed cube. It has been proven that has more attractive properties than other variations of the basic hypercube in terms of the smaller diameter, fewer edges, and lower cost factor. In this paper, we study the diagnosability of under the pessimistic diagnosis strategy based on two diagnostic models: the PMC model and the MM* model. And we obtain the following results: if, the diagnosability of the are both under the pessimistic diagnosis strategy based on the two models.